Insights into retinal hemangioblastoma using ultra widefield imaging - Kumar, Pradeep (Indian J Ophthalmol, 2019)
PURPOSE: Retinal hemangioblastomas (RHs) are characteristic of von Hippel-Lindau (VHL) disease. Early diagnosis of retinal lesions may aid in systemic diagnosis. Early identification of VHL is life-saving and also prevents vision loss. Fundus fluorescein angiography (FFA) is a useful tool in the diagnosis and management of RHs. The aim of this study is to report FFA features of RH using ultra-widefield (UWF) imaging. METHODS: A retrospective cross-sectional study of consecutive patients of RH who underwent UWF FFA at a tertiary eye care center. Images were analyzed and assessed by authors. The main outcome measures were (a) the number and size of RH in each eye and (b) vascular characteristics of the retina. UWF-FFA characteristics in each eye were tabulated. The number of clock hours involved by these characteristics and their correlation with the number and size of RH were analyzed. RESULTS: The study evaluated 24 eyes of 13 patients. The mean age was 28.4 years. The median number of RHs in an eye was 3.5 (range 1–16), and the size of RHs varied from 0.1 to 4 disc diameters. Novel UWF-FFA findings noted in this study were the presence of abnormal capillary network in 22 of 24 eyes (91.7%), capillary leakage in 15 of 24 eyes (62.5%), and capillary telangiectasia in 7 of 24 eyes (29.2%). In addition, feeder arterioles and venules showed bulbous projections in 8 of 24 eyes (33.3%). CONCLUSION: The UWF-FFA characteristics of RH, which have not been described before, were identified. These add to our understanding of the pathogenesis of the disease and may pave the way for future therapeutic targets.